Fine‐Tuning Aggregation of Nonfullerene Acceptor Enables High‐Efficiency Organic Solar Cells. Issue 9 (13th July 2021) - Xie, Yuanpeng; Ye, Linglong; Cai, Yunhao; Zhang, Xue; Xu, Jinqiu; Wang, Tao; Liu, Feng; Sun, Yanming
Abstract : Molecular aggregations of electron donor and electron acceptor are significantly important for light absorption, exciton separation, and charge transport, which determine the power conversion efficiency (PCE) of organic solar cells (OSCs). Herein, hot solution (HS) casting and thermal annealing (TA)‐dependent aggregation behaviors of a new nonfullerene acceptor (NFA), C10‐IT4F, are systematically investigated. Upon the TA treatment, the crystallization of C10‐IT4F is largely enhanced, and the active layer forms polyhedron crystals in 100 nm scale. This excessive aggregation prevents the exciton diffusion to DA interfaces and increases charge recombination, leads to a moderate PCE of 11%. In contrast, the HS treatment significantly improves the J‐aggregation of C10‐IT4F, and thus produces a new absorption feature in the near‐infrared region. As a result, OSCs processed by the HS method yield a high PCE of 14.2%. The results highlight the effect of processing methods on the molecular aggregation of NFAs and photovoltaic performance of OSCs. Abstract : Hot solution (HS) and thermal annealing (TA) processes‐dependent aggregation behaviors of a nonfullerene acceptor, C10‐IT4F, are systematically investigated. The TA treatment significantly increases the crystallization of C10‐IT4F and enables excessive aggregation. In contrast the HS treatment improves the J‐aggregation of C10‐IT4F, and thus produces a new absorption feature in the near‐infrared region, contributing to better photocurrent generation.